FOOD SOVEREIGNTY SORGUM: SINTESIS STRATEGI GREEN DIGITAL BRANDING DAN AKSELERASI EKOSISTEM PANGAN LOKAL MASA DEPAN - Dara Salsabila Rianti; Faizah Syahsiah Shofhah; Vina Meliana; Alyssa Nailu Farha; Makayla Prameswari Salsabila (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The transformation of the global food system faces the pressures of climate change, supply chain disruptions, and a dependency on imported food; these factors reinforce the urgency of food sovereignty based on adaptive local commodities. Sorghum possesses strategic potential as a future food source due to its resilience in marginal lands, water-use efficiency, and compatibility with sustainable bioeconomic systems. However, studies on sorghum development, the value-added potential of local food, and the digital transformation of agrifood remain fragmented, thus failing to form an integrative sustainability-based framework. This research aims to synthesize the strategic potential of sorghum as a commodity to strengthen food sovereignty, examine the role of Green Digital Branding in increasing the added value and competitiveness of sorghum products, and formulate an acceleration model for a sorghum-based local food ecosystem that is digitally integrated, sustainable, and collaborative. The study employs the Systematic Literature Review (SLR) method through the analysis of national and internationally indexed literature, utilizing inclusion-exclusion selection, study quality assessment, data extraction, and thematic synthesis. The analysis focuses on the agronomic-economic potential of sorghum, green branding of sorghum products, the digital agrifood ecosystem, and food sovereignty based on alternative food sources. The synthesis results indicate that sorghum's potential can be optimized by strengthening its economic value and production sustainability based on agroecological characteristics. The integration of Green Digital Branding enhances the competitiveness of sorghum products through sustainability narratives, digital supply chain transparency, and the strengthening of ecological identity. The acceleration model for a sorghum-based food ecosystem requires green financing, the digitalization of production, distribution, and consumption value chains, as well as multi-stakeholder collaboration to bolster a resilient local food system oriented toward long-term food sovereignty.